Islam, politics and youth in Malaysia the pop-Islamist reinvention of PAS - Müller, Dominik M. (Routledge contemporary Southeast Asia series, 2014)
Providing an ethnographic account of the Islamic Party of Malaysia (PAS) and its Youth Wing (Dewan Pemuda PAS), this book analyses the genesis and role of Islamic movements in terms of their engagement in mainstream politics. It explores the party's changing approach towards popular culture and critically investigates whether the narrative of a post-Islamist turn can be applied to the PAS Youth. The book shows that in contrast to the assumption that Islamic marketization and post-Islamism are reinforcing each other, the PAS Youth has strategically appropriated and integrated Islamic consumerism